TINJAUAN PADA CV. PURNAMA GEMILANG TERHADAP PENGAKUAN DAN METODE PENYUSUTAN ASET TETAP - Yustina Nainggolan; Emma Tampubolon; Emerald G.M. Tobing (Buletin Ekonomi, 2018)
To increase the expected production company must improve the quality good, where the existence of assets play an important role in the company's operations. This study aims to determine the recognition of fixed assets owned at CV. Purnama Gemilang are in accordance with SFAS No. 16 and to know the methods used in conducting the CV Fixed Assets depreciation. Purnama Gemilang. In undertaking this study, the authors observed directly on the CV. Purnama Gemilang to obtain data. Fixed assets at CV. Purnama Gemilang recognized when the future economic benefits can be obtained and its value can be reliably measured, whereas the depreciation method used by the CV. Purnama Gemilang in calculating the amount of depreciation expense by using the Straight Line Method (Straight Line Method). It means recognition and depreciation methods used in the CV. Purnama Gemilang in accordance with Statement of Financial Accounting Standards (SFAS) No. 16.Keywords :Assets, Operations, Recognition, Methods, Statement of Financial Accounting Standards (SFAS).